Nanograin–glass dual-phasic, elasto-flexible, fatigue-tolerant, and heat-insulating ceramic sponges at large scales. (April 2022) - Li, Lei; Jia, Chao; Liu, Ying; Fang, Ben; Zhu, Wenqing; Li, Xiaoyan; Schaefer, Laura–Alena; Li, Ziwei; Zhang, Fangshu; Feng, Xuning; Hussain, Naveed; Xi, Xiaoqin; et al.
Graphical abstract: Abstract: Ceramics are considered intrinsically brittle at room temperature, which is mainly attributed to the limited availability of crystallographic slips and pre-existing geometrical flaws. Moreover, the lack of flexibility has severely hindered many high-end applications of ceramic materials. Here, we produce ceramic sponges that are simultaneously ultra-light, elasto-flexible, thermally insulating, and can fully recover from large deformation with a near-zero Poisson's ratio. These spongy materials also possess superb fatigue resistance without the accumulation of damage or structural collapse for 10, 000 large-scale compressive or buckling cycles. We demonstrate the exceptional flexibility is enabled by the elastic distortion of nanograin–glassy dual phase and the fiber bulking in open-cell three-dimensional structure. Moreover, these spongy materials possess superior temperature-invariant superelasticity from deep cryogenic temperatures (−196 °C) to high temperature (1500 °C). Our study not only developed mechanically reliable lightweight ceramics for numerous extreme applications, but also provided new theoretical insights into the origin of flexibility in polycrystalline ceramics.